ANALISIS RASIO KINERJA KEUANGAN PADA KOPERASI UNIT DESA (KUD) MANUNGGAL DESA BANDAR PADANG KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Putri Setia Pamungkas; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted to determine and assess the performance of a cooperative. This research was conducted at the Koperasi Unit Desa (KUD) Manunggal Desa Bandar Padang using a quantitative descriptive research method. The data used in this study uses the time series method which comes from financial statements in the form of balance sheets and profit and loss between 2014 and 2018. Data analysis techniques in this study used quantitative analysis, namely analyzing financial statements with a financial ratio approach in the form of liquidity, solvency and profitability, then adjusted to the criteria for assessing the financial soundness of cooperatives. The results of the study show that the financial performance of cooperatives using the liquidity ratio at the Koperasi Unit Desa (KUD) Manunggal for five years from 2014-2018 seen from the current ratio and quick ratio is in the unhealthy category. Meanwhile, based on the solvency ratio, seen from the debt to equity ratio in 2014 to 2018, it is included in the unhealthy category. Meanwhile, based on the profitability ratio using net profit margin in 2014 to 2018, it is included in the unhealthy category. For profitability ratios analyzed by return on total assets and return on equity in 2014 to 2018 and are included in the unhealthy category. Based on the analysis of financial performance, it can be concluded that the performance of the Koperasi Unit Desa (KUD) Manunggal Desa Bandar Padang has not performed well and is less efficient. Keywords: Liquidity, Solvency, and Profitability